Abnormal findings in fetal echocardiography and maternal disease: A cross-sectional study - Mohammad Reza Alipour; Hossein Moradi; Seyedeh Mahdieh Namayandeh; Fatemeh Majidpoure; Zohreh Pezeshkpour; Mohammadtaghi Sarebanhasanabadi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Congenital cardiovascular malformation is the most common group of birth defects. Fetal echocardiography is highly sensitive and specific in the diagnosis of congenital heart disease in low- and high-risk populations. Objective: This study aimed to assess abnormal findings in fetal echocardiography and maternal disease. Materials and Methods: This cross-sectional study was performed on 114 pregnant women referred to Afshar hospital, Yazd, Iran from October 2016 to March 2017. All pregnant women underwent fetal echocardiography through fetal heart screening protocol, which is administered by the international society of ultrasound in obstetrics and gynecology guidelines. Data collected included referral cause, gestational age, maternal age, gravida, and final diagnosis after an accurate fetal echocardiography. Results: The mean gestational age was 20 wk. The most common referral cause of pregnant women included diabetes (36.8%), fetal arrhythmia (14%), high maternal age (7%), and echogenic focus on ultrasound (6.1%). The most common postpartum findings were normal (68.4%), cardiac abnormalities (17.6%), and arrhythmias (14%). In postnatal echocardiography, the results were consistent with fetal echocardiography except in 2 women. Conclusion: This study showed that fetal echocardiography can be used in the early diagnosis and treatment of congenital heart diseases.